Improved nursery practices and farmers’ willingness to adopt heat-tolerant tomatoes under tropical conditions - Asante, Bright O.; Osei, Michael K.; Bediako, Kwabena A.; Annor, Benjamin; Gyau, Joseph; Adomako, Joseph; Prempeh, Ruth N. (Frontiers in Sustainable Food Systems, 2024)
Heat tolerant tomato (Solanum lycopersicum L) can be used to alleviate the impact of climate variability, increase productivity and increase incomes of smallholder vegetable farmers under tropical conditions. Adoption of improved nursery practices and willingness to adopt heat tolerant tomato varieties under tropical conditions was examined. Using data from 432 tomato farmers, multivariate probit and tobit regression models were used to assess willingness to adopt heat tolerant varieties and the number of nursery practices adopted. Willingness to adopt heat tolerant tomato varieties was positively influenced by education, experience and extension contacts.Adoption of improved nursery practices was influenced by sex, household size, off-farm income, credit, education and extension. These results will enable decision makers to priotize strategies that target educated farmers with more years of experience in tomato production and have contacts with extension to enhance the adoption of heat tolerant tomato seeds with complementary improved nursery practices to increase productivity and incomes of smallholder tomato farmers producing under tropical conditions.